K2CO3-mediated anti-oxidation of solid amine CO2 adsorbents: Local microenvironment regulation and radical pathway inhibition - Fangzheng Zou; Xianxiang Bai; Hao Wu; Jiguang Li; Lingjun Tan; Xuehua Shen; Zuotai Zhang; Feng Yan (Chemical Engineering Journal, 2026)

Integrated analysis of muscle proteomics and neurotransmitter-targeted metabolomics in Penaeus vannamei infected with Enterocytozoon hepatopenaei (EHP) - Zhipeng Yin; Yajie Tian; Chuanyu He; Fan Yang; Dongchun Yan; Ting Li; Linrui Chang; Lingjun Si (Aquaculture, 2026)

Transcriptome analysis provides molecular evidence for muscle growth regulation in Litopenaeus vannamei infected with Ecytonucleospora hepatopenaei (EHP) - Chuanyu He; Zhipeng Yin; Yajie Tian; Fan Yang; Zheng Cao; Cuixia Wang; Dongchun Yan; Ting Li; Linrui Chang; Lingjun Si (Journal of Invertebrate Pathology, 2026)

Estimation of residual coal tar saturation in soils - Lingjun Kong; Peng-Fei Yan; Kurt D. Pennell (Journal of Hazardous Materials, 2026)

Extrusion-shaped PEI@B/MC-M560 adsorbents for direct air capture: Balancing mechanical strength and CO2 adsorption efficiency - Yixuan Lu; Jinsheng Zou; Lingjun Tan; Heijin Chen; Junhao Lin; Linying Huang; Xuehua Shen; Zuotai Zhang; Feng Yan (Journal of Cleaner Production, 2026)

EGDE-induced crosslinking of PEI@D500 adsorbents for direct air capture: Enhanced hydrothermal and oxidative stability - Linying Huang; Xianfeng Jiao; Junhao Lin; Jieyong Hao; Lingjun Tan; Duo Zeng; Shuoyu Wang; Yixuan Lu; Xuehua Shen; Zuotai Zhang; Feng Yan (Chemical Engineering Journal, 2026)

Dilation of the distal convoluted tubule induced by repeated heat exposure in rats model - Zhongyou Li; Taoping Bai; Wentao Jiang; Fei Yan; Lingjun Liu; Chong Chen (Journal of Thermal Biology, 2025)

Endocrine disruption of Triphenyl Phosphate via VIT-2 in Caenorhabditis elegans: A comparative analysis with estradiol and 4-hydroxytamoxifen - Chongli Shi; Mengyan Huang; Yang Zheng; Chen Wang; Hiu Yan Lam; Susu Wang; Lingjun Zeng; Yi Peng; Yulun Gu; Yu Li; Haibin Hao; Haibo Chen; et al. (Journal of Hazardous Materials, 2025)

Comparative transcriptome analysis of head kidney and gill with infection of spring viremia of carp virus in common carp (Cyprinus carpio) - Cuixia Wang; Yingying Zhang; Dongchun Yan; Lingjun Si; Linrui Chang; Ting Li (Aquaculture, 2025)

Associations of physical frailty and polygenic score with incident heart failure in cardiovascular patients: unraveling the mediating role of inflammation - Jiajin Chen; Sicheng Li; Shichen Bu; Xiaoqing Nie; Le Zhang; Lingjun Jie; Ya Fang; Cuilian Dai; Yan Wang (GeroScience, 2025)

Plant regeneration through somatic embryogenesis in Tilia cordata - Yin Li; Lingjun Yan; Huanli Wang; Shijie Tang (Plant Cell, Tissue and Organ Culture (PCTOC), 2025)

Effects of Enterocytozoon hepatopenaei infection on intestinal immune defense and physiological processes of Penaeus vannamei - Zheng Cao; Chuanyu He; Zhipeng Yin; Caiyi Chen; Fan Li; Dongchun Yan; Ting Li; Linrui Chang; Lingjun Si (Frontiers in Marine Science, 2025)
As the main pathogen causing growth retardation, EHP is considered to be mainly parasitic in the hepatopancreas of shrimp. However, the intestines of shrimp infected with EHP frequently exhibit syndromes such as jejunum and white midgut. Therefore, the challenge experiment was carried out in this study to compare the differences in intestinal histology, digestion and absorption, immune defense and oxidative stress of P. vannamei between the control group and EHP infection group. Histological analysis showed that EHP infection significantly damaged the intestine of the shrimp, including intestinal villus rupture and outer membrane impairment. Concurrently, EHP infection can trigger intestinal immune response, and the expression of key immune genes like Toll, myeloid differentiation factor, anti-lipopolysaccharide factor, and Relish was significantly enhanced, while the expression of IMD and alkaline phosphatase was suppressed. Additionally, antioxidant genes manganese superoxide dismutase, catalase, glutathione peroxidase, glutathione-S-transferase, and nuclear factor E2-related factor 2 were up-regulated to varying extents in EHP infection group, and the contents of lipid peroxides and malondialdehyde were heavily accumulated. Moreover, the expression levels of key genes involved in nutrient absorption, transport and synthesis, such as glucose transporter 1, Na + -K + ATPase, fatty acid synthase, acetyl-CoA carboxylase, rapamycin kinase, mTOR regulation-related protein, eukaryotic translation initiation factor 4E binding protein, ribosomal protein S6 kinase, were significantly up-regulated. However, the activities of amylase, lipase, and trypsin were inhibited in EHP infection group throughout the experiment. In summary, EHP infection damaged the intestine of P. vannamei , accompanied by immune response and oxidative stress. At the same time, nutrient transport and synthesis pathways were activated, while digestive enzyme activities were inhibited, indicating that in order to maintain survival, shrimps must accelerate material transport. Unfortunately, it remains in a state of nutrient deficiency that ultimately affects growth.

Assessment of microplastic exposure in nasal lavage fluid and the influence of face masks - Meng Zhang; Tingting Liu; Lujing Zhang; Zhenggang Hua; Ziqi Guo; Jiaxin Dong; Qinyue Tan; Yifei Xie; Xingru Yin; Lingjun Yan; Guowei Pan; Wei Sun (Journal of Hazardous Materials, 2024)

Electroluminescence aptasensor based on tetrahedral DNA nanostructure with exonuclease-assisted target cycling for detection of acetamiprid - Jingjing Liu; Lingjun Geng; Haifang Wang; Jingcheng Huang; Shuxian Zhou; Luting Yan; Lei Tian; Yaoting Mou; Pengwei Zhang; Junhao Zhao; Ziping Cai; Mingxin Zhao; et al. (Food Research International, 2024)

Promoting effects of ferric ions on Microcystis aeruginosa growth and arsenate accumulation and reduction at different phosphorus environments - Zhenhong Wang; Lingjun Zeng; Zhuanxi Luo; Yan Wang; Chunming Hao (Environmental Pollution, 2024)

GR/P300 Regulates MKP1 Signaling Pathway and Mediates Depression-like Behavior in Prenatally Stressed Offspring - Bin Wei; Yajun Shi; Xi Yu; Yongle Cai; Yan Zhao; Yueyang Song; Zejun Zhao; Ming Huo; Lingjun Li; Qinqin Gao; Dongyi Yu; Bin Wang; et al. (Molecular Neurobiology, 2024)

Molecular characterization and functional analysis of ZAP-like gene in common carp (Cyprinus carpio) - Yingying Zhang; Cuixia Wang; Dongchun Yan; Lingjun Si; Linrui Chang; Ting Li (Fish & Shellfish Immunology, 2024)

Modulating the chemical environment of Ni2+ for the oxidative dehydrogenation of ethane: The formation of LAS(Al3+/Ga3+)-Ni-OH site - Qinghui Li; Huahua Zhao; Jian Yang; Jun Zhao; Liang Yan; Huanling Song; Lingjun Chou (Chemical Engineering Journal, 2024)

Vertical transmission of aerosols between building flats through drainage system: A review - Min Chang; Di Mu; Yi Zhao; Lingjun Xiao; Yan Wu; Naiping Gao (Building and Environment, 2024)

Study on the detection of groundwater boundary based on the Trefftz method - Yan Su; Bin Huang; Lingjun Yang; Xiaohe Lai; Chuan Lin; Xiudong Xie; Lidan Hong (Natural Hazards, 2024)

Regulation of NF-κB signaling by NLRC (NLRC3-like) gene in the common carp (Cyprinus carpio) - Cuixia Wang; Jiahui Xu; Yingying Zhang; Dongchun Yan; Lingjun Si; Linrui Chang; Ting Li (Fish & Shellfish Immunology, 2024)

Dynamic effects of occupant motion on indoor vertical thermal stratification in the displacement ventilation system - Feng Lu; Xiao Lingjun; Chang Min; Wu Yan; Gao Naiping (Energy and Buildings, 2024)

Vapor-phase ethanol carbonylation over Ni supported on activated carbon: Influence of the textural properties and oxygen-containing groups - Wenbing Yang; Huahua Zhao; Huanling Song; Jian Yang; Jun Zhao; Liang Yan; Lingjun Chou (Chemical Engineering Journal, 2023)

Watershed land-use heterogeneity affecting spatial patterns of fish community structure in Han River basin, China - Xumeng Huo; Yan Xu; Fei Huang; Shu He; Yanpeng Cai; Lingjun Xiao (Journal of Cleaner Production, 2023)

Inflammation as a Mediator of Microbiome Dysbiosis-Associated DNA Methylation Changes in Gastric Premalignant Lesions - Lingjun Yan; Wanxin Li; Fenglin Chen; Junzhuo Wang; Jianshun Chen; Ying Chen; Weimin Ye (Phenomics, 2023)

Identification of CCCH-type zinc finger antiviral protein 1 (ZAP) gene from Pacific white shrimp (Penaeus vannamei): Characterization and expression analysis in response to viral infection - Yingying Zhang; Jiahui Xu; Jiyue Yu; Lingjun Si; Linrui Chang; Ting Li; Dongchun Yan (Fish & Shellfish Immunology, 2023)

Mechanistic and quantitative profiling of electro-Fenton process for wastewater treatment - Anliu Wang; Ying Jiang; Yiqi Yan; Lingjun Bu; Zongsu Wei; Richard Spinney; Dionysios D. Dionysiou; Ruiyang Xiao (Water Research, 2023)

Transcriptome analysis of the hepatopancreas in Penaeus vannamei under experimental infection with Enterocytozoon hepatopenaei (EHP) - Zheng Cao; Yang Gao; Jiahui Xu; Ning Yang; Ting Li; Linrui Chang; Lingjun Si; Dongchun Yan (Fish & Shellfish Immunology, 2023)

Detection of microplastics in domestic and fetal pigs’ lung tissue in natural environment: A preliminary study - Han Li; Zuosen Yang; Feng Jiang; Liang Li; Yansheng Li; Minmin Zhang; Zhenzhen Qi; Ruixue Ma; Yuanyuan Zhang; Jing Fang; Xi Chen; Yihang Geng; et al. (Environmental Research, 2023)

An Intra-Oceanic Subduction System Influenced by Ridge Subduction in the Diyanmiao Subduction Accretionary Complex of the Xar Moron Area, Eastern Margin of the Central Asian Orogenic Belt - Yang Cheng; Qinghui Xiao; Tingdong Li; Liquan Xu; Yuxu Fan; Yan Li; Lingjun Guo; Jinli Pang; Weiming Yuan (Journal of Earth Science, 2021)

Occurrence, Seasonal Variation and Risk Assessment of Antibiotics in the Surface Water of North China - Jiaxing Cheng; Lei Jiang; Tangqiang Sun; Yan Tang; Zhenxia Du; Lingjun Lee; Qiyue Zhao (Archives of Environmental Contamination and Toxicology, 2019)

Relationships of relative humidity with PM2.5 and PM10 in the Yangtze River Delta, China - Cairong Lou; Hongyu Liu; Yufeng Li; Yan Peng; Juan Wang; Lingjun Dai (Environmental Monitoring and Assessment, 2017)

Slab break-off model for the Triassic syn-collisional granites in the Qinling orogenic belt, Central China: Zircon U-Pb age and Hf isotope constraints - Zhiwei Bao; Christina Yan Wang; Lingjun Zeng; Weidong Sun; Junming Yao (International Geology Review, 2015)